PENGAWASAN BERBASIS ICT TERHADAP DISIPLIN KERJA PEGAWAI: PERAN MODERASI LITERASI DIGITAL DALAM KONTEKS WILAYAH PESISIR - Shalahuddin Shalahuddin; Nursia Nursia; Fakhruddin Kurnia M; Dedy Darmawan; Tiomy Butsianto Adi; Farida Islamiah (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the effectiveness of information and communication technology (ICT)-based monitoring on employee work discipline by considering the moderating role of digital literacy within the context of coastal areas. The study employs a systematic literature review approach using bibliometric analysis of 146 documents obtained from the Scopus database. The findings indicate that research on ICT and employee performance has shown a significant upward trend over the past decade and is predominantly concentrated in the fields of business and management. The thematic analysis reveals that ICT has the potential to improve work discipline through more transparent and real-time monitoring systems; however, its impact is not direct. The effectiveness of ICT is influenced by psychological factors, organizational conditions, and employees’ level of digital literacy. Additionally, ICT usage may also generate negative effects such as work stress and resistance to technology. This study highlights digital literacy as a moderating variable that strengthens the relationship between ICT-based monitoring and employee work discipline. Furthermore, the coastal context plays a crucial role in influencing ICT implementation due to limitations in infrastructure and technological access. This research contributes to the development of a conceptual model integrating ICT, digital literacy, and regional context in enhancing employee work discipline.